Strategi Pendidikan Islam Dalam Membentuk Generasi Berkarakter dan Berintegritas di Pondok Modern Darussalam Gontor Kampus 7 Kalianda Lampung Selatan - Iqbal Mustofa Fathurrahman; Megawati; Chairul Amriyah; Deti Elice (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze Islamic education strategies in shaping the character and integrity of students at Pondok Modern Darussalam Gontor Campus 7, Kalianda, South Lampung. Using a qualitative descriptive approach, this research explores the implementation of leadership training, entrepreneurship, and skill-based programs as core elements of character development. Data were collected through observation, interviews, and documentation to capture the holistic integration of spiritual, intellectual, and social values within the pesantren education system. The findings indicate that the institution successfully integrates Islamic principles with national values, creating a balanced model between academic excellence, moral integrity, and spiritual awareness. The implemented character education strategies foster students who are intellectually competent, emotionally mature, and spiritually grounded. Furthermore, the pesantren curriculum promotes independence, discipline, and responsibility through experiential learning and organizational involvement. In conclusion, the Gontor educational model represents an integrated approach to Islamic character education aligned with the national vision of building a virtuous and highly ethical generation toward Indonesia’s Golden Era 2045.